Mucinous Urothelial Carcinoma of the Renal Pelvis - Behzatğlu, Kemal (Rare Tumors, 2014)
Urothelial carcinoma with abundant myxoid stroma is a newly-described and extremely rare entity. Since only very few cases have been reported, there is no consensus on its nomenclature. Microscopic examination revealed invasive urothelial carcinoma with widespread low-grade noninvasive areas. There were focal invasive areas in the neighborhood of the renal parenchyma. Malignant urothelial tumor/cell groups localized in the stroma had abundant myxoid/mucinous background in the invasive areas. The cytoplasm of the tumoral cells was more eosinophilic in these areas and the cells formed small groups and cords. Histochemically, PAS and Alcian Blue were positive in the cytoplasm of the tumoral cells and in the stroma while negative in the non-mucinous areas. Immunohistochemically, the tumoral cells of the mucinous invasive areas diffusely expressed MUC1 and MUC2. We discuss the origin of the mucinous/myxoid stroma, the tumor’s nature and its nomenclature with histochemical and immunohistochemical features.